Exchange rate misalignment in selected Caribbean countries - Moore, Winston (Caribbean Centre for Monetary Studies [St. Augustine]TT, 2003)
Investigates whether the real effective exchange rates (REER) for Barbados, Jamaica and Trinida and Tobago over te period 1970-2001 are over or undervalued.